2014
DOI: 10.1371/journal.pone.0091636
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory, Th1, Th2, Th17 Cytokines and Dendritic Cells: A Cross-sectional Study in Chronic Periodontitis

Abstract: There are a limited number of studies correlating the different stages of dendritic cells (DC) maturation with cytokines in individuals presented chronic periodontitis (CP). The aim of the study was to evaluate the correlation among the expression of IL-2, IL-10, IL-4, IL-6, IFN-, TNF-α, and IL-17A with the presence of DC and mild-moderate or advanced CP. Gingival samples were obtained from 24 individuals with CP and six samples of normal mucosa (NM) overlapping third molar for controls of the levels of cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 54 publications
2
60
1
1
Order By: Relevance
“…In a study on mRNA expression of IL-17 and other cytokines in periodontitis and periodontally healthy specimens, Cardoso et al 24 found higher levels of IL-17 mRNA in periodontitis samples than in healthy controls. Souto et al, 25 who used flow cytometry to analyze cytokines in processed gingival biopsies, also reported on higher levels of IL-17 in periodontitis samples than in healthy gingiva. Although the reference samples or controls to periodontitis in the studies referred to above included both gingivitis and periodontally healthy tissues, the results agree with data reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on mRNA expression of IL-17 and other cytokines in periodontitis and periodontally healthy specimens, Cardoso et al 24 found higher levels of IL-17 mRNA in periodontitis samples than in healthy controls. Souto et al, 25 who used flow cytometry to analyze cytokines in processed gingival biopsies, also reported on higher levels of IL-17 in periodontitis samples than in healthy gingiva. Although the reference samples or controls to periodontitis in the studies referred to above included both gingivitis and periodontally healthy tissues, the results agree with data reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…IFNc can activate macrophages to release inflammatory cytokines, including TNF-a, interleukin (IL)-1b, and IL-6, which, at the end, leads to a chronic inflammatory condition (Monteleone et al, 2002). In periodontitis, increased levels of IFN-c, IL-2, IL-10, IL-17A, and TNF-a had been observed in several studies, demonstrating the participation of Th1/Th2/Th17 cell cytokines in the disease pathogenesis (Gaffen and Hajishengallis 2008;Souto et al, 2014). Therefore, the intensive hyperactive T-cell theory is perhaps seen as one most widely accepted connection between Crohn's disease and periodontitis (Indriolo et al, 2011).…”
Section: Similarities In Pathogenesis Of Crohn's Disease and Periodonmentioning
confidence: 99%
“…On the other hand, CD4+ T cells, differentiating into Th2 cells, express GATA3 and Stat6 and produce more IL-4, IL-5, and IL-13. In addition, CD4+ Th2 cells are part of a type-2 immune response, i.e., a type of immunity which is mainly involved in the removal of helminthes and extracellular parasites and facilitates B-cell antibody secretion (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Tregs express fork-head lineagespecific transcription factor (FoxP3) proteins and are able to secrete immunomodulatory cytokine, IL-10 (10). In addition to an imbalance in Th1/Th2 cells, a dysregulated immune response, related to Th17 and FoxP3+ Tregs, has been linked to certain types of cancer, particularly colon cancer (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%